Review and Analysis of Articles in the Field of Middle Age Literature - Ebrahim Namdari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the field of observing the standards of scientific papers, researchers take into account principles, rules, and specific criteria which depend on their skills, experience, and great carefulness. The present study aims to review the structure of six articles published in the Journal of Arabic Literature at Tehran University in the field of literature middle age, and their compliance with the standards of scientific papers. Research Standards related to the structure of scientific papers in these six articles suggest that some articles have drawbacks, such as having too general titles, lack of objective research methods in the abstract, weakness in key words, the lack of basic questions, lack of mentioning the literature and stereotypes of result.